Changes in electronic cigarette use and label awareness among smokers before and after the European Tobacco Products Directive implementation in six European countries: findings from the EUREST-PLUS ITC Europe Surveys. (12th September 2020) - Nikitara, Katerina; Girvalaki, Charis; Kyriakos, Christina N; Driezen, Pete; Filippidis, Filippos T; Kahnert, Sarah; Hitchman, Sara C; Mons, Ute; Fernández, Esteve; Trofor, Antigona C; Przewoźniak, Krzysztof; Demjén, Tibor; et al.
Abstract: Background: Article 20 of the European Tobacco Product Directive (TPD), which went into effect in May 2016, regulates electronic cigarettes (e-cigarettes) in the European Union (EU). The aim of this study was to evaluate changes in e-cigarette use, design attributes of the products used and awareness of e-cigarette labelling and packaging among smokers from six EU Member States (MS) before and after TPD implementation. Methods: Data come from Wave 1 (2016, pre-TPD) and Wave 2 (2018, post-TPD) of the ITC Six European Country Survey among a sample of smokers and recent quitters who use e-cigarettes from six EU MS. Weighted logistic generalized estimating equations regression models were estimated to test the change in binary outcomes between Waves 1 and 2 using SAS-callable SUDAAN. Results: In 2018, current daily/weekly e-cigarette use among adult smokers was just over 2%, but this varied from the highest in Greece (4%) to lowest in Poland (1.2%). From Waves 1 to 2, there was a significant increase in respondents reporting noticing and reading health and product safety information on leaflets inside e-cigarette packaging (8.39–11.62%, P < 0.001). There were no significant changes between waves of respondents reporting noticing or reading warning labels on e-cigarette packages/vials. Conclusions: e-cigarette use among smokers in these six EU countries is low. Although reported noticing and reading leaflets included in the packaging of e-cigarettes increased significantly from before to after the TPD, there was no significant change in reported noticing and reading of warning labels. Findings indicate the importance of continued monitoring of TPD provisions around e-cigarettes.